KEMEROSOTAN SEKTOR PERINDUSTRIAN PADA ZAMAN MAMLUK- SUATU ANALISIS SEJARAH DARI TEMPOH 872 H/1468 M HINGGA 922 H/1517 M - Mujani, Wan Kamal (Journal of Al-Tamaddun, 2008)
Industry played an important role in the economy of Egypt during the Mamlūk period. There were many kinds of industries which operated at that time, such as textiles, sugar, paper, glasswork and metalwork industries. Nevertheless, the period under discussion witnessed changes in industries where some of them were in a malaise situation. Hence, the aim of this article is to discuss the factors which affected the industrial sector during that time by using information narrated by the Mamlūk historians and the works written by modern scholars. The article identifies several factors which affected industry during that time, such as the Mamlūks’ attitude towards this sector. They monopolised all the industries and imposed heavy taxes on the civilian industrialists. The languor in industry was also due to the lack of technological innovation. This factor led to a competition from Europe side where technological innovation in many industrial sectors had been in progress from the end of eighth-fourteenth century. The recurrence of plague in Egypt during the period under review also affected the industrial sector. The resulting depopulation caused a shortage of workers which led to an increase in labour costs as well as the prices of industrial products.